The burden of infection with HSV-1 and HSV-2 in England and Wales: implications for the changing epidemiology of genital herpes. Issue 3 (1st June 2000) - Vyse, A J; Gay, N J; Slomka, M J; Gopal, R; Gibbs, T; Morgan-Capner, P; Brown, D W
Abstract : Objective: To measure the burden of infection with herpes simplex type 1 (HSV-1) and herpes simplex type 2 (HSV-2) in the general population of England and Wales and to assess temporal changes in the incidence of HSV-1 infection in childhood. Methods: 4930 residual blood samples taken from people aged 0–69 years and submitted to 15 public health laboratories in England and Wales between January 1994 and June 1995, and 500 samples taken from people aged 10–14 years between November 1986 and December 1987, were screened for IgG antibody to HSV-1 and HSV-2 using type specific ELISA assays. Results: The prevalence of antibody to HSV-1 in 10–14 year olds declined from 34% in samples collected in 1986–7 to 24% in samples collected in 1994–5 (p<0.001). HSV-1 antibody prevalence in adults increased with age and was higher in females than males, reaching 54% in females aged 25–30 years in 1994–5. In samples collected in 1994–5 from people aged 16–69 years HSV-2 antibody was detected in sera from 3.3% of men and 5.1% of women. Conclusions: The incidence of HSV-1 infection in childhood is falling in England and Wales. The prevalence of HSV-2 infection in the general population is low, with the rate of infection significantly lower than that described for the general population in the United States and developing countries. The falling rate of HSV-1 infection in childhood may be one factor contributing to the increasing incidence of genital HSV-1 infection.